EMPIRICAL ANALYSIS OF E-MODULE BASED ON SCIENCE LITERATION AS A SOURCE IN LEARNING ELECTROMAGNETIC RADIATION MATERIAL - Zurryati Syahputri; M. Rahmad; Mitri Irianti; Dina Veranita (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2019)
E-module based on scientific literacy of electromagnetic radiation material has been validated by experts, but this e-module has not been applied to students in learning in schools. This research aimed to determine the empirical validity of e-modules based on scientific literacy as a source of learning material for electromagnetic radiation. The research method used is the 4D method, namely: defining, design, development and dissemination. This research focuses on the development stage, that limited testing. The research data analysis technique used is descriptive analysis. Respondents from this research were class X students and teachers of Riau Province Integrated Agriculture Vocational School, totaling 23 students and 2 teachers. The research data were obtained using an empirical validity questionnaire instrument. The results of the analysis of the empirical validity test data of e-module based on scientific literacy which include design aspects, content aspects, pedagogical aspects, and technical aspects obtained an average score of 4.34 with a high validity category. So, it can be concluded that e-module based on scientific literacy as a source of learning material for electromagnetic radiation, is declared valid and can be used in learning for students in senior high schools or agriculture vocational high school.